The Mechanism of Action of Praziquantel: Can New Drugs Exploit Similar Mechanisms? - Thomas, Charlotte M.; Timson, David J. (Current Medicinal Chemistry, 2020)
Praziquantel (PZQ) is the drug of choice for treating infection with worms from the genus Schistosoma. The drug is effective, cheap and has few side effects. However, despite its use in millions of patients for over 40 years its molecular mechanism of action remains elusive. Early studies demonstrated that PZQ disrupts calcium ion homeostasis in the worm and the current consensus is that it antagonises voltage-gated calcium channels. It is hypothesised that disruption of these channels results in uncontrolled calcium ion influx leading to uncontrolled muscle contraction and paralysis. However, other experimental studies have suggested a role for myosin regulatory light chains and adenosine uptake in the drug’s mechanism of action. Assuming voltage-gated calcium channels do represent the main molecular target of PZQ, the precise binding site for the drug remains to be identified. Unlike other commonly used anti-parasitic drugs, there are few definitive reports of resistance to PZQ in the literature. The lack of knowledge about PZQ’s molecular mechanism(s) undermines our ability to predict how resistance might arise and also hinder our attempts to develop alternative antischistosomal drugs which exploit the same target(s). Some PZQ derivatives have been identified which also kill or paralyse schistosomes in culture. However, none of these are in widespread clinical use. There is a pressing need for fundamental research into the molecular mechanism( s) of action of PZQ. Such research would enable new avenues for antischsistosomal drug discovery.
Keywords: schistosomiasis